A Novel Ferroptosis-Related Gene Model for Overall Survival Predictions of Bladder Urothelial Carcinoma Patients - Zhang, Min; Zhang, Xin; Yu, Minghang; Zhang, Wei; Zhang, Di; Zeng, Song; Wang, Xi; Hu, Xiaopeng (Frontiers in Oncology, 2021)
Background: Bladder cancer is the most common urinary tract malignancy, and 90% of bladder tumors are urothelial cell carcinomas. Ferroptosis, a new form of cell death discovered in recent years, is an iron-dependent form of cell death characterized by the lethal intracellular accumulation of lipid-based reactive oxygen species. Ferroptosis is a double-edged sword for cancer and cancer therapy. Methods: The expression profile of bladder cancer (BLCA) was obtained from the Cancer Genome Atlas (TCGA) RNAseq database. Ferroptosis-related genes were downloaded from the FerrDb website. We identified ferroptosis-related differentially expressed genes (DEGs) that were related to overall survival (OS). The least absolute shrinkage and selection operator (LASSO) and multivariate Cox regression were utilized to develop a ferroptosis-related prognostic model (FRPM). A Nomogram model based on FRPM and clinicopathological features was constructed and validated. Furthermore, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and single-sample gene set enrichment analysis (ssGSEA) were utilized to compare DEGs between the high-risk and low-risk groups. RT-qPCR, CCK8 assay, and scratch assay were used to perform experimental verification. Results: A 7-gene FRPM was constructed to stratify patients into two groups according to the risk score. Survival analysis and time-dependent ROC analysis demonstrated that the model had stable performance. Multivariate Cox regression revealed that FRPM is an independent prognostic predictor for OS of BLCA patients and the results were displayed by a nomogram. ROC analysis, C-index, Calibration plots and DCA curves indicated that our nomograms enabled valuable predictions. Functional Enrichment analysis suggested that DEGs between low - and high-risk groups play a vital role in the progression of ferroptosis. ssGSEA indicated that immune status was different between the two groups. RT-qPCR confirmed the differential expression of DEGs in tissues. CCK8 assay and scratch assay confirmed the promoting effect of SCD on the proliferation and migration of tumor cells. Conclusion: Our study defined a novel prognostic model of 7 ferroptosis-related genes, which proved to be independently associated with OS of BLCA. A nomogram was developed to provide insight into the prediction of BLCA prognosis.